Method for developing databases being easily adaptable to changes in the subject domain - Yesin, V.I.; Vilihura, V.V. (Radiotekhnika, 2018)
A method for developing relational databases with the schema invariant to subject domains is proposed. The use of this method unlike the traditional technology of designing relational databases allows: creating databases for various simulated subject domains that meet the requirements of consumers of the information product in the process of reengineering, with less time and financial costs; adapting relational databases built on the basis of a scheme with a universal basis of relations to dynamic changes in subject domains, without changing the database schema, due to the use of the created predetermined structure of basic relations.